Victor Grant Collection, Album 2, Photograph 79 William Morrison III
Husband of Evelyn Maxwell who was the daughter of Ferd Maxwell.
Designation "2.79" in listing stands for Album 2, Photograph 79.
From collection of photographs compiled by Victor Grant, descendant of the Maxwell / Beaubien family.
Located in Office Closet
Keywords: Morrison, William III; Morrison, Evelyn Harriet Maxwell; Maxwell, Ferdinand; Maxwell, Caroline Matilda Allen; Maxwell - Beaubien family; Genealogy - Photographic collection. -- New Mexico